Fermentation method for vegetable waste into liquid organic fertilizer in Malangsuko Village - Ratna Juwita; Anindyah Sutra Karury; Muhammad Firdaus; Nikmatul Fitriyah; Meutya Nuraini; Algafari Bakti Manggara (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2024)
Malangsuko Village is one of the villages that produces quite a lot of horticultural crops such as vegetables. However, with this potential, Malangsuko village faces challenges in the use of inorganic fertilizers and the lack of organic waste management, especially vegetable waste which can pollute the environment. Seeing the existing potential and as a solution to these problems, the need for organic fertilizer can be made by utilizing vegetable waste in Malangsuko village. This activity aims to process organic waste from vegetable waste into liquid organic fertilizer (POC). The method of implementing this community service is carried out by training and mentoring the processing of organic waste into liquid organic fertilizer using the fermentation method. The results of the training and mentoring were an increase in partner skills, namely PKK women in Malangsuko village, making POC by 55%. The potential for processing organic waste in the form of vegetable waste into POC that partners can produce is two sacks of vegetable waste per day (± 50 Kg), so the amount of POC that partners can produce is 250 L per day.